(untitled) (Indian Journal of Animal Production and Management, 2014)
One hundred raw milk samples were collected randomly from 4 different villages of Proddatur mandal of Kadapa District in Andhra Pradesh to determine the physio – chemical properties. The organoleptic quality was conducted by a panel of experts as per standard score card and the chemical constituents were determined by EKOMILK – Ultra PRO milk analyzer. The results revealed that the milk samples from Kamanur village were slightly higher in fat, protein and solids not fat contents when compared with the rest of the other three villages.